LAGUNA BUATAN UNTUK WISATA PANTAI DITINJAU DART ASPEK GEOLOGI (Studi Kasus: Pantai Krakal, Kecamatan Tanjungsari, Kabupaten Gunung Kidul), Yogyakarta) = Artificial Lagoon for Beach Resort Based on Geological Aspect Case - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Krakal Beach is located in Tanjungsari, Gunung Kidul, Yogyakarta and is an interesting place for tourism activities. In 1997/1998, an artificial lagoon was built in this area to enchant the tourist resort areas. This research was intended to explain the role of geology and hydrogeology as a cause of failure of the artificial lagoon. The methods included field observations and laboratory analysis. Field observations were conducted to collect geological data (lithology and structural geology/joint system) and hydrological data such as percolation test. The Percolation test showed that field coefficient of permeability of fragmental limestone was 61.60 m/ day, while the field coefficient of permeability of limestone was 6.62 10-2 m/ day. From the result of laboratory analysis, it could be concluded that laboratory coefficient of permeability of limestone was 5.836 10.3 - 2.240 10-2 m/ day with porosity value of 8.00 - 16.13%. Due to the existance of joint system in the basement of the artificial lagoon which is built from limestone, so that most of surface water infiltrates into the ground to become groundwater in that area. As a result, the purpose of artificial lagoon for reservoir of saline water was not succeesful.